Psychiatric assessment in image-based sexual abuse case: a case report on imputability in personality disorder with narcissistic traits - Lorenzo Lodde; Claudia Zandara; Andrea Martella; Mirko Manchia; Mirko Manchia; Pasquale Paribello; Irene Mascia; Martina Pinna (Frontiers in Psychiatry)
ObjectivesCrimes committed on the Internet and social networks are rising, and the phenomenon is complex. Knowledge of context would be useful for professionals in cases that need psychiatric assessment. We report on a case of a 27-year-old young adult who is accused of image-based sexual abuse and other crimes, for whom the examining judge requested psychiatric assessment.MethodsWe conducted anamnestic collection (family, physiological and pathological, psychiatric, and toxicological), direct evaluation of the examinee, assessment of acquired health records, psychodiagnostic tests (i.e. graphic tests: Machover test, Koch test), Montreal Cognitive Assessment, Minnesota Multiphasic Personality Inventory 2, Pathological Narcissism Inventory, State-Trait Anger Expression Inventory 2, Toronto Alexithymia Scale, Thematic Apperception Test.ResultsThe clinical forensic assessment led to a diagnosis of Unspecified Personality Disorder (predominantly narcissistic traits) according to the DSM-5 criteria. Direct assessment showed a tendency to simulate or exaggerate symptoms, confirmed by the invalidation of the MMPI-2. In addition, the psychodiagnostic test showed a tendency to aggressive behavior and difficulty in identifying and describing emotions and feelings (alexithymia).ConclusionsThis case highlights the importance of being familiar with the context of the Internet and social networks, where a rising number of crimes are committed. Forensic psychiatrists will be increasingly involved in evaluating cases related to the online world, which requires a basic knowledge of its characteristics and dynamics.